Phyto Chemical Analysis and Anti Microbial Activity of Plant Extracts of Kalanchoe Pinnata - JASTI ASHA KUMARI (International Journal of Pharma and Bio Sciences, 2010)
Antiquated Ayurveda followed therapeutic plants as medicines to treat different sicknesses. They have extraordinary impact on treatment of different diseases without after effects. Therapeutic use of plant seeds, berries, roots, leaves, bark, and flowers is called herbal medicine. The study examined the antibacterial activity of Kalanchoe pinnata leaf methanolic and chloroform extract on Staphylococcus aureus, Pseudomonas aeruginosa, E. coli, and bacillus subtilis. Gram-positive bacteria respond better to methanolic extract. Kalanchoe pinnata chloroform extract inhibits E. coli and P. aeruginosa. Phytochemical screening of methanolic and chloroform extracts. However, this study found that plant leaves are highly antimicrobial against Gramme positive and Gram-negative bacteria.